Science, technology, and innovation policies to encourage women’s participation in steam: International experiences and lessons for Vietnam - Ta Doan Hai; Dang Thu Giang; Le Ngoc Hoa; Ha Manh Hung (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2025)
As the world enters the era of the Fourth Industrial Revolution, the STEAM fields (Science, Technology, Engineering, Arts, and Mathematics) play a critical role in innovation and sustainable economic growth. However, in many countries, including Vietnam, women’s participation in STEAM remains limited due to cultural, social, and educational access barriers. This underrepresentation not only diminishes the potential of a high-quality workforce but also hinders national competitiveness. This article analyzes international experiences from countries such as the United States, Australia, and Japan in promoting women’s involvement in STEAM and proposes policy solutions tailored to Vietnam’s socio-economic context. These solutions include: improving STEAM education, creating flexible working environments, raising public awareness, and enhancing financial support for women in research and innovation. These recommendations aim to foster sustainable development, promote gender equality, and strengthen national competitiveness. Code: 25020501